The Role of Teacher Interpersonal Behavior on Learning Outcomes in The Cognitive, Affective, and Moral Domains - Lestari, Gyan Puspa; Syihabuddin; Kosasih, Aceng; Somad, Momod Abdul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Students' academic abilities are not only influenced by students' innate abilities but are also influenced by the learning environment created by teachers. This research aims to test the validity of the teacher interpersonal behavior questionnaire designed by researchers and determine the role of each teacher's interpersonal components on cognitive and affective development and student morale. This research uses factorial design analysis to look at the role of teachers' interpersonal skills on students' cognitive, affective, and moral abilities. The participants involved in this research were 550 junior high school students. Data was collected using questionnaires to assess teachers' interpersonal skills, cognitive self-report, affective, and student moral assessment scales. Data analysis uses multiple regression and correlation analysis to see the correlation between these variables. The research results show that students' perceptions of teachers' interpersonal skills significantly correlate with learning outcomes in students' cognitive, affective, and moral domains. Apart from that, the questionnaire scale designed by the researcher meets the validity criteria because the questionnaire scale can explain what scales are positive and negative predictors of student learning outcomes in each domain. This research implies that teachers must display positive interpersonal behavior during the learning process or interaction with the class so that the learning process is more effective.